The Role of Folk Pedagogical Legacy in the Education of the Youth - Yu.E. Purkhanov (Zien Journals, 2023)
The article talks about folk pedagogical legacy, including ancient written sources, the importance of the educational views of thinkers in the education of modern youth.
Keywords: Avesto; folk pedagogy; pedagogical views